2016
DOI: 10.2495/cmem-v4-n1-1-12
|View full text |Cite
|
Sign up to set email alerts
|

Dispersed two-phase flow in a gas–liquid cylindrical cyclone separator

Abstract: The performance of a gas-liquid cylindrical cyclone separator for the separation of air bubbles from hydraulic fluid has been analyzed numerically using the commercial computational fluid dynamics flow solver CFX. Two-phase flow behavior is modeled based on an Eulerian-Eulerian approach, representing both liquid and dispersed gas phase as interpenetrating media with interphase momentum transfer captured based on existing bubble drag models. Only a single bubble size is considered for the dispersed phase and bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Mehring's recent study explored different boundary conditions and turbulence models, concluding that the pressure outlet serves as a suitable boundary condition for the cyclone outlet. Additionally, the study found that the Best-Simon Leith Eddy-Resolved Simulation Model (BSL ERSM) turbulence model produced favorable qualitative results [9].…”
Section: Introductionmentioning
confidence: 99%
“…Mehring's recent study explored different boundary conditions and turbulence models, concluding that the pressure outlet serves as a suitable boundary condition for the cyclone outlet. Additionally, the study found that the Best-Simon Leith Eddy-Resolved Simulation Model (BSL ERSM) turbulence model produced favorable qualitative results [9].…”
Section: Introductionmentioning
confidence: 99%